Simulation and Parametric Study of a Multiple Effect Distillation with Thermal Vapour Compression - Zakaria, Irnie Azlin; Abdul Rahman, Siti Mariam; Chong, Edilson Marqueles (International Journal of Integrated Engineering, 2025)
Desalination plants are widely used in industrial applications, such as oil and gas, food and beverage, and power generation industries, to produce clean water for internal use. This gives industries greater control over their water security. The project aims to simulate the mathematical model for a Multiple Effect Distillation with Thermal Vapour Compression (MED-TVC) with constraints, incorporating mass and energy balances and the seawater’s thermodynamic properties. The model was simulated using MATLAB to compare the production rate of clean water and gain output ratio (GOR) with different configurations of the desalination system. Input factors considered in the simulation include seawater to evaporator feed flow rate, seawater intake flow rate, seawater salinity, and seawater temperature. The simulation was validated by comparing it with available data of MED-TVC plants from SIDEM with 98.85% accuracy. Results show that the variation in temperature of each evaporator (increment and reduction from -30% to +50% of initial temperature) influences clean water production. Based on the simulation, the vapour output increases as the evaporator’s temperature rises, thus increasing the GOR and total distillate production. These findings highlight the critical role of evaporator temperature in optimizing MED-TVC system performance, providing valuable insights for improving industrial desalination processes.